The principle of fair trial and criminalistics knowledge of the public prosecutor - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The work is divided into three major parts. In the first part, the author discusses the principle of a fair trial in criminal proceedings. In the second part, the author deals with the problem of knowledge of public prosecutors in the field of criminalistics. The third part is the conclusion, in which the author points out that the state of the art equipment, methods or legislation cannot bring the desired results, if the public prosecutor does not have the necessary expertise and knowledge, primarily knowledge on criminalistics.